Behavior Analysis and Stunting in Children: A Case-Control Study - Herawati, Cucu; Charien Rahayu Lestari; Iin Kristanti; Suzana Indragiri; Awis Hamid Dhani; Nuniek Tri Wahyuni; Supriatin (Department of Nutrition, Faculty of Health Sciences, Universitas Brawijaya Malang, 2024)
Stunting is a significant issue that can impact a child’s future quality of life, affecting both brain and physical development, as well as adult productivity and learning capacity. Behavioral factors play a critical role in stunting prevalence. This study aims to examine how behavioral factors affect stunting in children under the age of five. A case-control study design was used, with a population of 118 stunted children. The sample consisted of 30 stunted children as the case group and 30 non-stunted children as the control group, selected through purposive sampling. Data were collected through interviews, and analysis was conducted using Odds Ratio and bivariate analysis. The results showed a significant correlation between stunting and maternal awareness (p = 0.007; OR = 4.571), a history of exclusive breastfeeding (p = 0.004; OR = 4.929), and dietary factors (p = 0.018; OR = 3.596). However, there was no significant correlation between stunting and maternal education level (p = 0.108; OR = 0.416). Children without a history of exclusive breastfeeding were nearly five times more likely to experience stunting (OR = 4.929). It is recommended that community health centers (Puskesmas) enhance health promotion efforts to prevent stunting linked to parental behavior.